Human glioma cells transformed by IGF-I triple helix technology show immune and apoptotic characteristics determining cell selection for gene therapy of glioblastoma. Issue 4 (1st August 2001) - Ly, A; Duc, H T; Kalamarides, M; Trojan, L A; Pan, Y; Shevelev, A; François, J-C; Noël, T; Kane, A; Henin, D; Anthony, D D; Trojan, J
Abstract : Aims —Insulin-like growth factor type I (IGF-I) antisense cellular gene therapy of tumours is based on the following data: rat glioma or hepatoma cells transfected with the vector encoding IGF-I antisense cDNA lose their tumorigenicity and induce a tumour specific immune response involving CD8 + T cells. Recently, using the IGF-I triple helix approach in studies of tumorigenicity, major histocompatibility complex class I (MHC-I) antigens were demonstrated in rat glioma transfected cells. This study used comparative IGF-I antisense and triple helix technologies in human primary glioma cells to determine the triple helix strategy that would be most appropriate for the treatment of glioblastoma. Methods —The cells were transfected using the IGF-I triple helix expression vector, pMT-AG, derived from the pMT-EP vector. pMT-AG contains a cassette comprising a 23 bp DNA fragment transcribing a third RNA strand, which forms a triple helix structure within a target region of the human IGF-I gene. Using pMT-EP, vectors encoding MHC-I or B7 antisense cDNA were also constructed. Results —IGF-I triple helix transfected glioma cells are characterised by immune and apoptotic phenomena that appear to be related. The expression of MHC-I and B7 in transfected cells (analysed by flow cytometry) was accompanied by programmed cell death (detected by dUTP fluorescein terminal transferase labelling of nicked DNA and electron microscopic techniques). Cotransfection of these cells with MHC-I and B7 antisense vectors suppressed the expression of MHC-I and B7, and was associated with a pronounced decrease in apoptosis. Conclusion— When designing an IGF-I triple helix strategy for the treatment of human glioblastoma, the transfected tumour cells should have the following characteristics: the absence of IGF-I, thepresence of both MHC-I and B7 molecules, and signs of apoptosis.